2017
DOI: 10.1016/j.oraloncology.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Improving accuracy of RNA-based diagnosis and prognosis of oral cancer by using noninvasive methods

Abstract: RNA-based diagnosis and prognosis of squamous cell carcinoma has been slow to come to the clinic. Improvements in RNA measurement, statistical evaluation, and sample preservation, along with increased sample numbers, have not made these methods reproducible enough to be used clinically. We propose that, in the case of squamous cell carcinoma of the oral cavity, a chief source of variability is sample dissection, which leads to variable amounts of stroma mixed in with tumor epithelium. This heterogeneity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…To establish a miR as a biomarker with a highly reliable assay system for routine clinical purposes, four conditions are needed. One, the examination of the biomarker should be easy and the method should be reproducible for clinical use ( 122 ). Two, many examination cases are needed ( 10 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish a miR as a biomarker with a highly reliable assay system for routine clinical purposes, four conditions are needed. One, the examination of the biomarker should be easy and the method should be reproducible for clinical use ( 122 ). Two, many examination cases are needed ( 10 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three, noninvasive methods should be preferred ( 123 ). Four, tissues should be accurately collected ( 122 ). Moreover, as described above, we should pay attention to the characteristics of the miRs.…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of those with reduced dysplasia, Cyclin D1 and Vascular Endothelial Growth Factor (VEGF) mucosal levels decreased [ 24 ]. Brush biopsy offers a noninvasive and validated method optimized for miRNA measurement of oral epithelial cells [ 47 ]. After 4 weeks of GT drinking, human tissue exposed to probably the highest concentration of undiluted tea in the body, the tongue epithelium, showed on average no changes in gene expression due to inter-subject variability in levels of miRNA.…”
Section: Significance Of Studying Gt Effects In Vivomentioning
confidence: 99%
“…For example, Wang et al performed LCM to collect intratumoral cell subgroups from different parts of the tumor (ITF, center, surface) and found that LOH on 9p21 (RPS6) was more frequently detected in ITF than at the center and surface [ 130 ]. Notably, brush biopsy is a noninvasive approach for the acquisition of tumor cells and can effectively solve the problem caused by intratumor heterogeneity, which is probably an optimal method for the early diagnosis of OSCC [ 131 ].
Fig.
…”
Section: Heterogeneity and Homogeneity Should Be Consideredmentioning
confidence: 99%